2015
DOI: 10.1108/ijoem-11-2011-0102
|View full text |Cite
|
Sign up to set email alerts
|

Consumer ethnocentrism and consumer animosity: antecedents and consequences

Abstract: Purpose – Consumer ethnocentrism and consumer animosity provide marketing management with two useful concepts to understand the reasons behind consumers’ purchase decisions concerning domestic vs imported products. The purpose of this paper is to investigate the antecedents and consequences of animosity and ethnocentrism within a single model, and respondents’ evaluations of a specific product category are solicited. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
88
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 38 publications
13
88
2
3
Order By: Relevance
“…This implies consumers' unwillingness to buy a product from a particular country that is perceived as the offending country, independently of consumers' judgments about the quality of the products originating from that particular country. Therefore, consumers may have a positive attitude towards the quality of the products produced in a particular country, but due to their animosity towards that particular country they are unwilling to buy these products (Fernández-Ferrín, Bande-Vilela, Klein & del Río-Araújo, 2015;. It is important to note that there are disagreements among the authors over this particular issue since the findings obtained in some studies show that animosity may also affect product judgments, as well as purchasing decisions (Lee & Lee, 2013).…”
Section: Implications Of the Animosity And Patriotism In Terms Of Conmentioning
confidence: 58%
See 1 more Smart Citation
“…This implies consumers' unwillingness to buy a product from a particular country that is perceived as the offending country, independently of consumers' judgments about the quality of the products originating from that particular country. Therefore, consumers may have a positive attitude towards the quality of the products produced in a particular country, but due to their animosity towards that particular country they are unwilling to buy these products (Fernández-Ferrín, Bande-Vilela, Klein & del Río-Araújo, 2015;. It is important to note that there are disagreements among the authors over this particular issue since the findings obtained in some studies show that animosity may also affect product judgments, as well as purchasing decisions (Lee & Lee, 2013).…”
Section: Implications Of the Animosity And Patriotism In Terms Of Conmentioning
confidence: 58%
“…Ovaj osećaj implicira izbegavanje kupovine proizvoda iz određene zemlje, pri čemu on ne utiče na potrošačevo negativno rasuđivanje o tim proizvodima. Time, potrošači mogu imati pozitivan stav o kvalitetu datih proizvoda, ali zbog antipatije koju osećaju prema zemlji njihovog porekla, oni izbegavaju kupovinu datih proizvoda (Fernández-Ferrín, BandeVilela, Klein & del Río-Araújo, 2015;. Ipak, važno je istaći da postoje nesuglasice među autorima i po ovom pitanju, budući da je u pojedinim studijama dokazano da animozitet može imati uticaj na rasuđivanje o samom proizvodu, a ne samo na kupovno ponašanje (Lee & Lee, 2013).…”
Section: Odnos Animoziteta I Patriotizma Prema Potrošačkom Etnocentrizmuunclassified
“…Questionnaire items referred to the dimensions of experts. For the customer ethnocentrism dimensions, this study used the dimensions from [16], namely cognitive, affective, and normative, while the dimensions of purchase decisions were from [3], namely product choice, brand choice, dealer choice, purchase timing, purchase amount, and payment method. Questionnaires were then tested their validity and reliability, which after being proven valid and reliable, they were then distributed to respondents.…”
Section: Methodsmentioning
confidence: 99%
“…The dimensions of Customer ethnocentrism are cognitive, affective, and normative [16]. 1) Cognitive, is a knowledge of the individual against the influence that occurs on foreign competition [17], 2) Affective, Acharya Elliot in [18] suggested that ethnocentrism refers to a group which had positive feelings toward their own group and negative feelings on other groups, 3) Normative, in the concept of customer ethnocentrism, is a great thing to do for the customer with regards to the practice of their consumption, that they should strive to prevent the negative influence from foreign competition [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore unsurprising that, through a review of studies across North American, European and Asian samples, both nationalism and patriotism have been regularly identified as antecedents to consumer ethnocentrism (Fernández-Ferrín et al, 2015). Conservatism (characterised by a desire to uphold tradition and the social order) has also been shown as leading to ethnocentrism, along with xenophobia and perceived personal and economic threat (Altintaş & Tokol, 2007;Balabanis et al, 2002;Fernández-Ferrín et al, 2015).…”
Section: Consumer Ethnocentrismmentioning
confidence: 99%